Phosphorus and heavy metals concentration in the river sediment along the river Vardar course - Melovski, Ljupčo; Levkov, Zlatko; Krstić, Svetislav (Macedonian Journal of Ecology and Environment, 1997)
The results of the phosphorus and heavy metals (Fe, Mn, Zn, Cu, Pb, Co and Cd) content investigation in the river sediment along the river' Vardar course are presented in this paper. Undoubtedly, the results that were obtained, confirm the suggestion that the concentration of phosphorus and heavy metals in the river sediment is better parameter for establishing of anthropogenous influence on the river ecosystem than their content in the river water.. By these results the disturbances in the algal populations along the river Vardar course can be explained more easily. The highest concentrations of almost all heavy metals and phosphors were established in the sediment of sampling points in Veles. On the contrary, the former' results of phosphors, nitrogen and heavy metals concentration in the river water showed the highest values in sampling points in the Skopje city and after industrial waste water inflow of the chemical industry "Veles".